Sadiq and the pet problem - Nuurali, Siman (Nuurali, Siman. Sadiq., 2020)
Sadiq's third grade class decides that they want a classroom pet, and their teacher, Ms. Battersby, is okay with the idea, so the students form a club to decide what kind of pet to get, and to research how to take care of it.